2003
DOI: 10.3322/canjclin.53.6.356
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Internet on Cancer Outcomes

Abstract: Each day, more than 12.5 million health-related computer searches are conducted on the World Wide Web. Based on a meta-analysis of 24 published surveys, the author estimates that in the developed world, about 39% of persons with cancer are using the Internet, and approximately 2.3 million persons living with cancer worldwide are online. In addition, 15%to 20% of persons with cancer use the Internet "indirectly" through family and friends. Based on a comprehensive review of the literature, the available evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
459
3
17

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(493 citation statements)
references
References 86 publications
14
459
3
17
Order By: Relevance
“…(2006), tanı almış kanser hastalarının %67'sinin internet yolu ile bilgi edindiğini bulmuştur. [26] Eysenbach (2003), kanser hastalarının internet kullanım oranlarının yüksek olduğunu vurgulamıştır. [27] Günümüzde internet kullanımı günden güne artmaktadır.…”
Section: Kanser Hastalarının Bilgi Kaynaklarıunclassified
See 1 more Smart Citation
“…(2006), tanı almış kanser hastalarının %67'sinin internet yolu ile bilgi edindiğini bulmuştur. [26] Eysenbach (2003), kanser hastalarının internet kullanım oranlarının yüksek olduğunu vurgulamıştır. [27] Günümüzde internet kullanımı günden güne artmaktadır.…”
Section: Kanser Hastalarının Bilgi Kaynaklarıunclassified
“…[26] Eysenbach (2003), kanser hastalarının internet kullanım oranlarının yüksek olduğunu vurgulamıştır. [27] Günümüzde internet kullanımı günden güne artmaktadır. İnternet kullanımının yaygınlaşmasıyla bloglar web kullanıcılarının bilgi paylaşımı için majör bir platform haline gelmiştir.…”
Section: Kanser Hastalarının Bilgi Kaynaklarıunclassified
“…18 Eysenbach suggests that healthcare professionals should acknowledge that patients are independently seeking information and therefore teach patients how to analyse and fi lter this information. 19 The Journal of the American Dental Association have published guidelines for patients regarding oral health information on the Internet. 20 Patients were encouraged to be cautious about information available online, to question the source, qualifi cations of the provider and the scientifi c validity of that which they read.…”
Section: Age Categoriesmentioning
confidence: 99%
“…44 Other advantages of OSGs over faceto-face groups include the absence of geographical and mobility barriers, anonymity for sensitive issues and the possibility of patients with rare conditions finding peers. 84 Disadvantages of the OSG vary from the volume of email received to lack of in-person contact. In some circumstances, OSGs may exacerbate a participant' s feelings of social isolation and reduced psychological wellbeing instead of strengthening a sense of social support.…”
Section: Acceptability Of Videoconferencingmentioning
confidence: 99%
“…In some circumstances, OSGs may exacerbate a participant' s feelings of social isolation and reduced psychological wellbeing instead of strengthening a sense of social support. 84 One study reported significantly higher levels of depression in oncology patients who take part in OSGs compared with those who attended face-toface support group meetings. 85 This uncontrolled cross sectional study had methodological constraints and the extent to which the Internet plays a causal or contributory role in the association with depression was not demonstrated.…”
Section: Acceptability Of Videoconferencingmentioning
confidence: 99%